Local detection of enhanced hot electron scattering in InSb/CdTe heterostructure interface - Xiaoxiao Ma; Zhenghang Zhi; Weijie Deng; Tianxin Li; Qianchun Weng; Xufeng Kou; Wei Lu (AIP Advances)
The InSb/CdTe heterojunction material, characterized by low effective mass and high electron mobility, exhibits interfacial energy band bending, leading to the Rashba spin–orbit coupling effect and nonreciprocal transport, which make it suitable for the fabrication of spintronic devices with broad applications in logic and storage fields. However, the complex heterojunction interfaces of InSb/CdTe, composed of group III–V and group II–VI semiconductors, are prone to interdiffusion. Therefore, characterization and study of the interfacial properties of InSb/CdTe heterojunctions are crucial for the growth improvement of the InSb/CdTe material system as well as its application in the field of spintronics. In this study, a novel scanning probe , called a scanning noise microscope, is applied to visualize hot electron scattering in InSb/CdTe nano-devices. The results demonstrate that the near-field signal originates from the Coulomb scattering of charged ions on electrons at the interface of the embedded layer heterojunction. This real-space, nondestructive characterization of the heterojunction interface properties offers a new tool for enhancing the performance of heterojunctions.